2009
DOI: 10.1016/j.biosystemseng.2009.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Gait and force analysis of provoked pig gait on clean and fouled concrete surfaces

Abstract: Gait and force analysis have proven to be useful methods in linking claw injuries to surface material conditions. To determine the relationship between claw disorder and floor properties such as friction and surface abrasiveness, the factors controlling gait must be characterised.The effects of fouled concrete floor conditions on the gait of 10 pigs walking in a curve, using kinematics and kinetics to record gait parameters and slip frequency are described and compared with clean conditions. Pigs adapted to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…This could be explained by the use of clay, which had to be slightly wet to produce a good footprint and may have appeared slippery to the sows. Indeed, studies on the gait of pigs walking on different types of floor showed that pigs shortened their stride length and speed when they walked on a slippery surface (von Wachenfelt et al, 2009). Therefore, the use of a slippery surface in the present study may have prevented the discrimination of lame sows from non-lame ones.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This could be explained by the use of clay, which had to be slightly wet to produce a good footprint and may have appeared slippery to the sows. Indeed, studies on the gait of pigs walking on different types of floor showed that pigs shortened their stride length and speed when they walked on a slippery surface (von Wachenfelt et al, 2009). Therefore, the use of a slippery surface in the present study may have prevented the discrimination of lame sows from non-lame ones.…”
Section: Discussionmentioning
confidence: 84%
“…It is studied using video recording where the subject's body is schematised with markers. Both of these methods have been used in pigs to evaluate gait and study the impact of floor friction level (von Wachenfelt et al, 2009), but they have never been used to quantify lameness in sows yet. Footprint analysis using high-resolution floor mat to record foot pressure has also been used to analyse gait in pigs, to compare different floor friction and identify which region of the claw is the most subject to stress (Carvalho et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This may be expected to be worse in on-farm situations where individual pig assessment is impeded within a pen with other pigs. Previous quantitative studies have investigated the instantaneous gait adjustment of pigs on slippery and nonslippery surfaces by means of gait analysis with force plates and 2D video kinematics (Thorup et al, 2008;von Wachenfelt et al, 2009). However, there appears to be no longitudinal study quantifying the gait and gait variability of pigs exposed to different commercial floor types for an extended part of their development.…”
Section: Introductionmentioning
confidence: 99%
“…Selection of proper sampling time intervals for accurate AI measurement of certain animal species should consider the velocities of both continuous movements (e.g., walking and running) and discrete movements (e.g., pecking, touching, smelling, dashing, etc.). A sampling time interval of 0.03 s has been used for cows [ 19 , 21 ], 0.04 s for pigs [ 20 , 22 ], and 0.2 s and 0.3 s for poultry [ 10 , 12 , 23 ].…”
Section: Discussionmentioning
confidence: 99%